Cell‐free fetal DNA analysis in maternal plasma as screening test for trisomies 21, 18 and 13 in twin pregnancy. (13th August 2018) - Le Conte, G.; Letourneau, A.; Jani, J.; Kleinfinger, P.; Lohmann, L.; Costa, J.‐M.; Benachi, A.
ABSTRACT: Objectives: To evaluate in twin pregnancy the utility of non‐invasive prenatal testing using circulating cell‐free fetal DNA (cfDNA) in screening for the three main autosomal fetal trisomies. Methods: cfDNA testing was offered to 492 patients with a twin pregnancy without ultrasound anomaly as a first‐line screening test or after routine serum screening. Data were collected prospectively and a retrospective analysis was performed. cfDNA analysis was performed by massively parallel sequencing. The fetal‐fraction threshold used for test evaluation was 8%. Regression analysis was performed to investigate the effect on the test failure rate of maternal and pregnancy characteristics, and the performance of the test was also reported. Results: cfDNA analysis was performed as a first‐line test (after the first‐trimester scan) in 377 patients and following serum screening in 115. Of the 420 pregnancies for which outcome was available and cfDNA screening was assessed, 78.7% were dichorionic–diamniotic. The test failed on the first attempt in 12 (2.9%) pregnancies, and regression analysis demonstrated that only maternal weight was a significant independent predictor of test failure. A result was subsequently achieved in the 10 cases for which a second sample was obtained. cfDNA analysis identified all three cases of trisomy 21 and the only case of trisomy 18. For trisomy 21, the specificity was 99.8% (95% CI, 98.7–100.0%). When considering pregnancies according to whether they were conceived spontaneously or after assisted reproductive technology, there were no significant differences in terms of maternal weight or no‐result rate for cfDNA screening between these two groups. Conclusions: In twin pregnancy without fetal ultrasound abnormality, cfDNA screening for trisomies 21, 18 and 13 had a high success rate and good performance. Therefore, in routine practice, cfDNA analysis could be considered as a first‐ or second‐line screening test. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.